Health examination-important opportunity for prevention. - Sithisarankul, P. (Chulalongkorn Medical Journal, 2023)
Preventive medicine classifies disease prevention into 3 levels- primary, secondary, and tertiary. Health examination, usually includes physical and laboratory examinations, carries high cost and usually aims at secondary prevention. The author emphasizes primary prevention in physical examination by reducing risk factors rather than detecting diseased persons. Modifiable risk factors are the main targets. Primary prevention should also be expanded to families and co-workers.